Analisis CR,DER,ROE DAN DPR TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEIPERIODE 2017 - 2021 - Nasution, Yuslinda; Septian, Rizki Andri (Jurnal Manajemen, 2024)
The purpose of this study was to determine the effect of CR, DER, ROE, and DPR on Stock Returns on businesses. The sample consists of 17 businesses in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2017-2021, selected through purposive sampling method. Data analysis involves descriptive approaches and multiple linear regression. The data used is secondary. partial test results state that the variables Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE) partially affect Stock Returns, and Dividend Policy (DPR) has no effect on Stock Returns. And the overall test results prove that variables such current ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Dividend Policy (DPR) all influence Stock Returns.